Identification of Secondary Metabolite Compounds from Melandean (Bridelian micrantha) Leaf Extract - Bayani, Faizul; Kurniasari, Baiq Anting; Hamdani, Ade Sukma; Yuliana, Depi; Wahyuni, Ida; Mujaddid, Jamilul (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The Melandean plant or Bridelia micrantha (Hochst.) Baill is traditionally used by the community to treat various human diseases, such as poisoning, paralysis, digestive diseases, diabetes, syphilis, and other diseases. Bridelia micrantha is believed to have active chemical compounds in the form of secondary metabolites which are useful for treatment. This active chemical compound is contained in the roots, leaves, seeds, skin, stems, and fruit. Bridelia micrantha leaves were used as samples in this study to analyze the secondary metabolite compounds contained therein. Leaf extraction was carried out using 80% methanol solvent through a maceration process. Analysis was carried out qualitatively using the phytochemical screening test method and quantitatively using the thin layer chromatography test method. Based on the results of the phytochemical screening test carried out, it is known that Bridelia micrantha is positive for containing active compounds in the form of flavonoids, tannins, saponins, and alkaloids. The results of the thin layer chromatography (TLC) test showed that flavonoid compounds were found with an Rf value of 0.437, tannin compounds with an Rf value of 0.312, saponin compounds with an Rf value of 0.625, and alkaloid compounds with Rf values of 0.125, 0.187, 0.312 and 0.5.